A single very low dose of intrathecal morphine with fentanyl as a useful adjunct to patient controlled analgesia in patients undergoing lumbar spine surgery: An interventional pilot study / Poh Yeh Han - Poh , Yeh Han (2017)
There have been many studies addressing intrathecal morphine (ITM) use following spine surgery published attempting to identify the optimal dose of ITM as an effective adjuct to intravenous patient controlled analgesia (PCA) post lumbar surgery. Primary aim: To determine whether administration of low dose morphine (0.1 mg) plus fentanyl (25mcg) intrathecally (ITMF) is a useful adjunct to PCA for providing postoperative pain control following elective lumbar spine surgery in adult population. Methods: A total of 18 patients were recruited for this trial. These patients were scheduled to undergo lumbar spine surgery under general anaesthesia. They were divided into Group I; receiving intrathecal morphine fentanyl prior to induction of general anaesthesia and group C; receiving intraoperative iv morphine at 0.lmg/kg (or at discretion of anaesthetist) upon skin closure. The patients were evaluated post operatively at 2,4, 6, 8, 12, 24 hours. Results: The intervention group reported much lower mean VAS scores at rest and bending leg and the scores were largely maintained throughout postoperative periods. The mean scores for side effects such as motor block, nausea/ vomit. pruritis, and sedation were similar for both intervention and control groups. Total PC A morphine use was significantly lower in the ITMF group. Conclusions: ITMF may be a useful adjunct to PCA morphine m post lumbar surgery with minimal opioid related complications.